Congenital Triangular Alopecia: A Case of Effective Response with 5% Topical Minoxidil in a Male Adolescent - Sutisna FD; Gondokaryono SP; Dwiyana RF; Effendi RMRA; Tache N; Anandita R (Dove Medical Press, 2024)
Frizam Dwindamuldan Sutisna, Srie Prihianti Gondokaryono, Reiva Farah Dwiyana, Raden Mohamad Rendy Ariezal Effendi, Nisrina Tache, Rafithia Anandita Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran, Hasan Sadikin Hospital, Bandung, IndonesiaCorrespondence: Srie Prihianti Gondokaryono, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +62 817114116, Email prihianti@gmail.comAbstract: Congenital triangular alopecia (CTA) is a rare entity of non-cicatricial alopecia characterized by triangular or oval-shaped alopecia patches on the frontotemporal region of the scalp. Few therapeutic options exist, and there is currently no effective treatment except for hair transplantation. We report the case of an adolescent boy with CTA who was treated with 5% topical minoxidil solution. During therapy, the patient showed improvement in the form of the appearance of terminal hairs, which started to show after two months of treatment. After eight months of treatment, the affected area was fully covered with dense terminal hairs. The patient did not report any adverse reactions/side effects.Keywords: Congenital triangular alopecia, minoxidil, trichoscopy